This Place Is Full of It: Towards an Organizational Bullshit Perception Scale. Issue 1 (February 2022) - Ferreira, Caitlin; Hannah, David; McCarthy, Ian; Pitt, Leyland; Lord Ferguson, Sarah
This study evaluated the psychometric properties of the Organizational Bullshit Perception Scale (OBPS) using two samples of employees of organizations in various sectors. The scale is designed to gauge perceptions of the extent of organizational bullshit that exists in a workplace, where bullshit is operationalized as individuals within an organization making statements with no regard for the truth. Analyses revealed three factors of organizational bullshit, termed regard for truth, the boss and bullshit language . The three factors are consistent with existing literature in the field of organizational bullshit and offer further insight into how employees view workplace bullshit. The OBPS constitutes three subscales measuring these factors. Future researchers should seek to validate the OBPS and further develop the identified factors of organizational bullshit.